Pharmacological Screening Of Combined Extract Of Annona Squamosa And Nigella Sativa - F V MANVI; B K NANJAWADE; SANJIV SHING (International Journal of Pharma and Bio Sciences, 2011)
Anti-arthritic, anti-inflammatory and analgesic activity of combined extract of Annona squamosa and Nigella sativa was evaluated and validated in various animal models. Arthritis was induced by Complete Freund`s Adjuvant (CFA) injection in metatarsal footpad of Sprague-Dawley rats. Degree of inflammation was evaluated by hind paw swelling and body weight, estimation of AST, ALT and TP supported by histopathology of knee joint. Combined extract reduced hind paw swelling, body weight, AST, ALT and TP Histopathology revealed significant reduction in mononuclear infiltration, pannus formation and bone erosion. Combined extract decreased the paw volume in carageenan treated rats. Combined extract (PHF) shows moderate central and peripheral analgesic activities in hot plate method and acetic acid induced writhing method in mice.